Surface plasmon resonance screening of synthetic peptides mimicking the immunodominant region of C-S8c1 foot-and-mouth disease virus - Gomes, P (1999)
The main antigenic site (site A) of foot-and-mouth disease virus (FMDV, strain C-S8c1) may be adequately reproduced by a 15-peptide with the amino acid sequence H-YTASARGDLAHLTTT-NH2 (A15), corresponding to the residues 136-150 of the viral protein VPI. The effect of amino acid substitutions within A15 on its antigenicity towards monoclonal antibodies (MAb) raised against antigenic site A, has been studied by means of BIAcore technology, based on surface plasmon resonance (SPR). Although these antigenicities have previously been determined from enzyme-linked immunosorbent assays (ELISA), the SPR-based technique is superior in that it allows a fast and straightforward screening of antigens while simultaneously providing kinetic data of the antigen-antibody interaction. With a view to screening fairly large libraries of individual peptides, we have inverted the typical SPR experiment by immobilizing the MAb on the sensor surface and using peptides as soluble analytes. We report the validation of this approach through the screening of 44 site A peptides, with results generally in good agreement with the relative antigenicities previously determined by competition ELISA.